Notes from a public typewriter - Gustafson, Michael, (Bookstore proprietor); Uberti, Oliver (Grand Central Publishing, 2018)
A collection of confessional, hilarious, heartbreaking notes written anonymously on a public typewriter for fans of PostSecret and Other People's Love Letters. When Michael Gustafson and his wife Hilary opened Literati Bookstore in Ann Arbor, Michigan, they put out a typewriter for anyone to use. They had no idea what to expect. Would people ask metaphysical questions? Write mean things? Pour their souls onto the page? Yes, no, and did they ever. Every day, people of all ages sit down at the public typewriter. Children perch atop grandparents' knees, both sets of hands hovering above the metal keys: I LOVE YOU. Others walk in alone on Friday nights and confess their hopes: I will find someone someday. And some leave funny asides for the next person who sits down: I dislike people, misanthropes, irony, and ellipses... and lists too. In NOTES FROM A PUBLIC TYPEWRITER Michael and designer Oliver Uberti have combined their favorite notes with essays and photos to create an ode to community and the written word that will surprise, delight, and inspire.